Long Non-coding RNA SENP3-EIF4A1 Functions as a Sponge of miR-195-5p to Drive Triple-Negative Breast Cancer Progress by Overexpressing CCNE1 - Chen, Lie; Miao, Xiaofei; Si, Chenchen; Qin, An; Zhang, Ye; Chu, Chunqiang; Li, Zengyao; Wang, Tong; Liu, Xiao (Frontiers in Cell and Developmental Biology, 2021)
Triple-negative breast cancer (TNBC) has high malignancy and limited treatment, so novel molecular therapeutic targets are urgently needed. Cyclin E1 (CCNE1) promotes progression in breast cancer, but its role and inherent mechanisms in TNBC are yet to be elucidated. Competing endogenous RNA (ceRNA) may be a potential mechanism. CCNE1 was selected though bioinformatics and clinical samples and cell lines were utilized to verify CCNE1 expression by qRT-PCR and western blot. Predicting tools provided potential miR-195-5p and SENP3-EIF4A1 and tested from multi-level. Functional experiments were conducted in vitro and in vivo. Luciferase reporter assay and RNA immunoprecipitation experiments were implemented to ensure the interaction between miR-195-5p and SENP3-EIF4A1/CCNE1 in TNBC. Bioinformatics found DNA hypermethylation of miR-195-5p and preliminarily verified. Mechanistically, SENP3-EIF4A1-miR-195-5p-associated ceRNA could drive TNBC progress though regulating CCNE1. DNA hypermethylation of miR-195-5p might be another reason. In summary, SENP3-EIF4A1-miR-195-5p-CCNE1 axis promotes TNBC progress and it may contribute to the novel diagnosis and treatment of TNBC.